Religious Moderation-Based Curriculum Development Management Perspective of Lecturers of Non-Religious Courses at UIN Maulana Malik Ibrahim Malang - Devi Pramitha; Dessy Putri Wahyuningtyas; Jamilah Jamilah; Mohammad Mahpur; Farida Isroani (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
Religious moderation is one of the policies of the Ministry of Religious Affairs which is expected to be implemented through curriculum design in the university, especially in the Semester Learning Plan. UIN Maulana Malik Ibrahim Malang one of the campuses that became a pilot project for the implementation of religious moderation policy conducted a baseline study to identify the process of elaboration and internalization as well as to design RPS based on religious moderation. This research uses qualitative methodology with data collection techniques consisting of in-depth interviews, documentation studies, and focus group discussions. The data obtained were then analyzed through a 3-stage interactive model, namely data condensation, data presentation, and conclusion drawing. The results of research related to religious moderation-based curriculum management in the process of elaboration and internalization based on the perspective of non-religious course lecturers include: (1) the planning stage in preparing learning outcomes and study materials related to religious moderation both explicitly and implicitly; (2) the implementation stage by designing a learning process related to religious moderation; and (3) the evaluation stage is carried out based on the formula of the lecturer concerned because the implementation of this religious moderation-based curriculum has not been fully implemented.